The cost-effectiveness of 10 antenatal syphilis screening and treatment approaches in Peru, Tanzania, and Zambia. (June 2015) - Terris-Prestholt, Fern; Vickerman, Peter; Torres-Rueda, Sergio; Santesso, Nancy; Sweeney, Sedona; Mallma, Patricia; Shelley, Katharine D.; Garcia, Patricia J.; Bronzan, Rachel; Gill, Michelle M.; Broutet, Nathalie; Wi, Teodora; et al.
Abstract: Objective: Rapid plasma reagin (RPR) is frequently used to test women for maternal syphilis. Rapid syphilis immunochromatographic strip tests detecting only Treponema pallidum antibodies (single RSTs) or both treponemal and non-treponemal antibodies (dual RSTs) are now available. This study assessed the cost-effectiveness of algorithms using these tests to screen pregnant women. Methods: Observed costs of maternal syphilis screening and treatment using clinic-based RPR and single RSTs in 20 clinics across Peru, Tanzania, and Zambia were used to model the cost-effectiveness of algorithms using combinations of RPR, single, and dual RSTs, and no and mass treatment. Sensitivity analyses determined drivers of key results. Results: Although this analysis found screening using RPR to be relatively cheap, most (> 70%) true cases went untreated. Algorithms using single RSTs were the most cost-effective in all observed settings, followed by dual RSTs, which became the most cost-effective if dual RST costs were halved. Single test algorithms dominated most sequential testing algorithms, although sequential algorithms reduced overtreatment. Mass treatment was relatively cheap and effective in the absence of screening supplies, though treated many uninfected women. Conclusion: This analysis highlights the advantages of introducing RSTs in three diverse settings. The results should be applicable to other similar settings.